Efficacy of Green Mussel Shell-Derived Hydroxyapatite as a Bone Graft Substitute in Rabbit Femoral Defects: An In Vivo Study - Rafika Syah Putra; Najatullah; Selamat Budijitno (HM Publisher, 2025)
Bone grafting is a standard procedure in fracture management to enhance bone healing using osteogenic, osteoinductive, and osteoconductive materials. Bovine hydroxyapatite (HA) is a commonly used bone substitute, but its production can be expensive. Green mussel shells have emerged as a potential alternative source of HA due to their abundance and lower cost, particularly in Indonesia. This study aimed to evaluate the efficacy of HA derived from green mussel shells on bone healing in rabbit femoral defects through radiological examination. A post-test only experimental study was conducted on male New Zealand white rabbits (n=36) with surgically created femoral defects. The rabbits were randomly divided into three groups: a control group (K) with no treatment, a group (P1) treated with bovine HA, and a group (P2) treated with HA derived from green mussel shells. Bone healing was assessed radiologically at weeks 2, 4, and 6 post-surgery using the Radiographic Union Score for Tibial Fractures (RUST) score on femoral X-rays. Statistical analysis was performed to compare the RUST scores between the groups and across the different time periods, with a p-value of <0.05 considered significant. Significant differences in RUST scores were observed between the groups at week 2 (K: 1.33 ± 0.50, P1: 2.67 ± 0.50, P2: 2.78 ± 0.44; p<0.001) and week 4 (K: 2.22 ± 0.44, P1: 3.11 ± 0.33, P2: 3.33 ± 0.50; p=0.003). However, no significant difference was found between the P1 (bovine HA) and P2 (green mussel shell HA) groups at these time points (p>0.05). At week 6, no significant differences in RUST scores were detected among all three groups (p=0.087). In conclusion, the findings of this study suggest that the efficacy of HA derived from green mussel shells in promoting bone healing in rabbit femoral defects is comparable to that of bovine HA, as assessed by the RUST score. This highlights the potential of green mussel shells as a cost-effective and readily available alternative source for HA in bone graft applications.